Educational Background and Teaching Experience Against PAUD Learning Design - Hermelina Abarua; Junita L Kundre; Mirdayati Aihena; Midarti Aihena (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Educational background is an important component in the education workforce to be able to understand and provide the best for students according to the field to be delivered. This study aims to look at the educational background on the ability to develop Ambon City PAUD Learning Design, teaching experience on the ability to develop Ambon City PAUD learning plans, and find out the relationship between the two on the ability to develop Ambon City PAUD learning plans. The approach used in this study is a quantitative approach to the correlational design (relationship), the population is PAUD teachers in Kec. In the Nusaniwe City of Ambon, totaling 134 teachers, the sample in this study is 20% of the population so the number of samples is 67 people. Data is collected through Questionnaires (Questionnaires) and documentation. There is a significant relationship between educational background and teaching experience on the ability to develop early childhood learning designs with r count = 0.2369 r table = 0.244. Based on the results of the analysis that has been done, it can be concluded that each variable has a significant relationship to the results of the ability to compose learning programs.